Accounting of water in different systems of rice cultivation - Shahane, Amit Anil; Shivay, Y S (Indian Farming, 2018)
Accounting of water per unit rough, brown and milled-rice produced helps in selecting suitable system of cultivation and quantifying the effect of Zn fertilization and microbial inoculation on water saving. The system of rice intensification requires less water per unit of rice produced in first year due to lower water used than PTR per kg of rice produced and higher productivity than aerobic rice system; while in second year, aerobic rice system stand superior in reducing water requirement than both SRI and PTR due to lower water used in aerobic rice system per kg of rice produced. Yield improvement due to Zn fertilization and application of microbial inoculation indirectly contribute to saving water. Hence, need due consideration while deciding water saving rice production systems.